Sustainable development and credit unions in economic and social profitability: a bibliometric analysis - Ximena Patricia Granizo Espinoza; María Alexandra Procel Silva; Samantha Anai Granizo Silva; Doménica Patricia Lalama Freire (Heritage and Sustainable Development)
Credit unions are key players in promoting sustainable development by incorporating economic, social, and environmental aspects into their structure and operation. Their holistic approach goes beyond the mere pursuit of financial profitability, also embracing the generation of positive social impact and environmental preservation. The present study sets out to examine in depth the compatibility between credit unions and the principles of sustainable development. To achieve this objective, an exhaustive literature review was conducted, involving the compilation, synthesis and critical analysis of various data sources related to the topic. This process made it possible to identify the various roles that these cooperatives can play as catalysts for positive change in the communities where they operate. It was found that they not only offer inclusive financial services but also foster community participation and promote sustainable practices both in their operations and in their investment decisions. The results obtained highlight the transformative potential of credit unions in the quest for more equitable and sustainable development. By adopting an approach that prioritizes not only economic profitability but also social and environmental well-being, credit unions emerge as key agents in advancing a comprehensive development agenda.